Machine learning security and privacy:a survey - Lei SONG; Chunguang MA; Guanghan DUAN (网络与信息安全学报)
As an important method to implement artificial intelligence,machine learning technology is widely used in data mining,computer vision,natural language processing and other fields.With the development of machine learning,it brings amount of security and privacy issues which are getting more and more attention.Firstly,the adversary model was described according to machine learning.Secondly,the common security threats in machine learning was summarized,such as poisoning attacks,adversarial attacks,oracle attacks,and major defense methods such as regularization,adversarial training,and defense distillation.Then,privacy issues such were summarized as stealing training data,reverse attacks,and membership tests,as well as privacy protection technologies such as differential privacy and homomorphic encryption.Finally,the urgent problems and development direction were given in this field.